'There's this glorious pill': gay and bisexual men in the English midlands navigate risk responsibility and pre-exposure prophylaxis. Issue 5 (20th October 2019) - Williamson, Iain; Papaloukas, Periklis; Jaspal, Rusi; Lond, Benjamin
ABSTRACT: Pre-exposure prophylaxis (PrEP) is currently being trialed for seronegative gay and other men who have sex with men (GMSM) at risk of HIV infection in England. However, research from other countries where PrEP is available shows limited literacy and uptake by GMSM at risk of HIV. We collected focus group data from 18 GMSM (13 HIV− and 5 HIV+) from Leicester, an ethnically diverse city in the English Midlands. Data were analysed using thematic analysis and three themes are presented. The first theme ' I can't get my head around people like that ': Representations of PrEP users within and beyond gay communities explores how PrEP users are vilified by some GMSM and the wider media. The second theme, 'There's a culture of anti-trust': PrEP, stigma and the interpersonal politics of HIV disclosure discusses how PrEP influences HIV disclosure and sexual decision-making in casual sero-discordant sexual encounters in a context where seropositive men experienced pervasive HIV stigma and HIV− men were suspicious of HIV+ sexual partners. In the final theme, ' I'm still suspicious': Discourses of doubt and distrust participants voiced concern over the safety of PrEP and the motives of drug companies, healthcare agencies and PrEP activists. We consider these findings through a critical lens of wider theorising around the relationship between public health agencies and GMSM communities and consider the impact of these perspectives on likely engagement with PrEP in an English context. We call for more critically informed and nuanced ways of promoting health and well-being amongst men from these communities.